Criminal Law Policy on Environmental Crimes in Climate Change Issue - SANCAYA, Wayan Werasmana; SAPUTRA, Komang Adi Kurniawan (Journal of Tourism Economics and Policy, 2025)
Climate change caused by human activities such as deforestation and pollution is a serious global issue. In Indonesia, despite the existence of the Environmental Protection and Management Law, the enforcement of environmental criminal law is still weak due to light sanctions, overlapping regulations, and corruption. This study assesses the effectiveness of environmental criminal policy in Bali related to climate change through an analysis of Regional Regulation No. 5/2011 and empirical data from interviews and court decisions. The results show that the environmental criminal law framework has not explicitly criminalized activities that cause climate change, such as carbon emissions from land conversion, and existing sanctions are not commensurate with ecological losses. Empirically, only 20% of environmental cases result in imprisonment, while 80% are resolved administratively. The main obstacles include economic pressure from the tourism industry, limited capacity of the apparatus, and conflicts between national and customary laws. This study recommends revision of regulations to include aspects of climate change, the establishment of a Special Environmental Court, and the integration of customary sanctions. These findings contribute to the green criminology literature and offer a Balinese Eco-Legal Framework model to balance tourism development and environmental protection. Without strong policy intervention, Bali is at risk of losing its ecological carrying capacity.